Understanding the Effect of a Healthcare Provider‑Led Family Planning Support Intervention on Contraception use and Pregnancy Desires among Postpartum Women Living with HIV in Southwestern Uganda - Atukunda, Esther Cathyln; Matthews, Lynn T; Musiimenta, Angella; Agaba, Amon G; Najjuma, Josephine N.; Lukyamuzi, Edward John; Kaida, Angela; Obua, Celestino; Mugyenyi, Godfrey Rwambuka (Springer, 2021)
Modern contraceptive prevalence among women living with HIV (WLWH) in Uganda is still low at 45%, and up to a third of women are likely to discontinue the method within the first year of initiation. This increases risks of unplanned pregnancies, perinatal HIV transmission and pregnancy complications. We aim to explore and explain the mechanism of effect of a family planning support intervention investigated in a randomized controlled trial conducted between October 2016 and June 2018 among 320 postpartum WLWH at a referral hospital in Southwestern Uganda that led to improved uptake, decreased contraception discontinuation and lowered pregnancy rates. Thirty WLWH and 10 of their primary sexual partners who participated in this trial were purposively selected and interviewed in the local language; interviews were digitally recorded. Translated transcripts were generated and coded. Coded data were iteratively reviewed and sorted to derive descriptive categories using an inductive content analytic approach. Up to 83% of women wanted to avoid pregnancy within the first year postpartum. Qualitative data showed that contraception uptake and use were influenced by: 1) Participant awareness and understanding of different methods available; 2) Participant perception of offered health services; 3) Healthcare provider (HCP) socio-cultural sensitivity to individual experiences and (mis)conceptions surrounding contraception; 4) Having tactile engagement, follow-up reminders and a reference to prompt action or discussions with partners. Supportive and culturally sensitive HCPs and systems facilitated information sharing leading to increased patient awareness and understanding of the contraceptive methods, and improved health user experience, care engagement, confidence and willingness to take up and continue using modern contraceptive methods.
Understanding the Effect of a Healthcare Provider‑Led Family Planning Support Intervention on Contraception use and Pregnancy Desires among Postpartum Women Living with HIV.
Keywords: Adherence intervention · Family planning support · Uganda · WLWH · Social support